2019
DOI: 10.1111/josh.12787
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of an Unstructured and Structured Approach to Increasing Recess Physical Activity

Abstract: BACKGROUND:The purpose of this study was to evaluate an unstructured and a structured program designed to increase physical activity (PA). The unstructured program increased the amount of equipment during recess, whereas the structured program introduced activities to students. METHODS:PA was observed using the System for Observing Play and Leisure Activity in Youth (SOPLAY) in two school districts in Colorado. Researchers recorded baseline and follow-up observations for sedentary activity, moderate PA, and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…47,48 It can also be equipment-based by providing new resources for students. 49 Similarly, policies can be fitness-based as a school-level goal, partner-based through collaboration, or CSPAP-based with PA opportunities provided throughout the school day. 15,23,28 This review summarizes the evidence within broad CSPAP-related categories and includes examples showing how schools are tailoring implementation based on available resources and community capacities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…47,48 It can also be equipment-based by providing new resources for students. 49 Similarly, policies can be fitness-based as a school-level goal, partner-based through collaboration, or CSPAP-based with PA opportunities provided throughout the school day. 15,23,28 This review summarizes the evidence within broad CSPAP-related categories and includes examples showing how schools are tailoring implementation based on available resources and community capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of recess, for example, can involve providing PA‐promoting activities or can be infrastructure‐based by changing landscapes or upgrading playgrounds 47,48 . It can also be equipment‐based by providing new resources for students 49 . Similarly, policies can be fitness‐based as a school‐level goal, partner‐based through collaboration, or CSPAP‐based with PA opportunities provided throughout the school day 15,23,28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The provision of equipment and supervision, particularly adult supervision during PA opportunities was shown to be significantly related to increased MVPA as reported across 8 studies. [27][28][29][30][31][32] In contrast, 2 studies found no significant change in PA with the presence of supervision or inclusion of equipment. 33,34 Participants and Settings Of the 60 studies analyzed, 75% (n = 45) reported the number of individuals observed, and 43.3% indicated the proportion of participants by gender and 58.3% identified them by race and/or ethnicity (Table 1).…”
Section: Research Designs and Physical Activitymentioning
confidence: 93%
“…Tématu "lifestylových sportů" jsme se věnovali v naší práci (Janeckova et al 2021), která naznačila, že aktivity jako skateboarding či parkour mohou zásadním způsobem přispět k vyšší úrovni pohybové aktivity a redukci sedavého chování. Na významu nestrukturovaných aktivit pro celkovou pohybovou aktivitu dětí se shodují také jiní autoři (Bangsbo et al, 2016;Behrens et al, 2019;Appelhans & Li, 2016), zvláště pak v případě, pokud se jedná o aktivity v přírodním prostředí, a to jak u dětí (Lovelock et al, 2016), tak u mladých dospělých (Morrow, Rodriguez & King, 2017).…”
Section: Organizované Volnočasové Aktivityunclassified